Pengaruh Motivasi Kerja dan Gaya Kepemimpinan terhadap Kinerja Pegawai pada Dinas Pertanian dan Ketahanan Pangan Kabupaten Nduga - Fita Dwi Oktaria; Yosephina Ohoiwutun; Muhlis Hafel (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to partially test and identify the influence of work motivation on performance; to test and determine the impact of leadership style on performance partially; and to test and identify the influence of work motivation and leadership style on performance simultaneously at the Nduga Regency Agriculture and Food Security Service. This type of research is quantitative research, with a sample of 49 respondents. The research instrument used in this research is a questionnaire. The research results show that work motivation partially has a positive and significant effect on performance; Leadership style partially has a negative and significant effect on performance, work motivation, and leadership style simultaneously have a positive and significant effect on performance. In conclusion, there is an influence of work motivation, leadership style, partially and simultaneously on work performance Keywords: Work Motivation, Leadership Style, Performance